Model Kemitraan dalam Pembangunan Rumah Sewa Swadaya - Sigit Wijaksono (Bina Nusantara University, 2012)
The high prices of land causes the decreasing development of rental housing around activity centers such as workplaces, schools and others. The specific objective of this study is to identify and map the forms of existing partnerships between government, business, and community organizations in the construction of rental housing, to identify obstacles in the implementation and effectiveness of these partnerships, and to develop a partnership model that can include and involve all interests (stakeholders) either from the government (central or local), businesses, and communities, as well as their respective roles in realizing the construction of rental housing for low income community. This study implements is a qualitative method with exploratory descriptive and comparative approach. Data are obtained through surveys in several locations as representatives of existing forms of self-help construction of rental housing in Jakarta, West Java and Batam. Data collection technique used observation and interviews are supported by direct observation in the field. The model developed is aimedat promoting self-help development of affordable rental housing which involves a partnership among government, business, and society. The partnership should be beneficial to all three parties. It should also allow affordability of low-income community to rent the house in the form of licensing component funded by national and local government, construction financed by the business or government, while the land acquisition component can use the land the community or local government.